Experimental methods : an introduction to the analysis persentation of data - Kirkup, L. (John Wiley and Sons, 1994)
This book is about: Introduction to experimentation; Characteristics of experimental data; Graphical presentation of data; Dealing with uncertainties; Statistical approach to variability in data; ...